153 Perampanel in patients with a history of psychiatric illness: a post hoc analysis. Issue 6 (27th May 2022) - Malhotra, Manoj; Patten, Anna; Kanner, Andres M
Abstract : Background: Psychiatric safety data from perampanel randomised controlled trials (RCTs; Studies 304/305/306/335) and open-label extensions (OLEx; Studies 307/335 OLEx) in patients with focal epilepsy with/without psychiatric history were analysed. Methods: Treatment-emergent adverse events (TEAEs) were analysed for patients with/without psychi- atric history. Results: In RCTs, 352/2187 (16.1%) patients had psychiatric history; psychiatric TEAEs occurred in 73/244 (29.9%) and 21/108 (19.4%) patients with perampanel and placebo, respectively. Psychiatric TEAEs with perampanel 2 and 4 mg/day were 11.1% and 15.4%, respectively, vs placebo (19.4%). In patients without psychiatric history, psychiatric TEAEs were observed in 157/1325 (11.8%) and 47/510 (9.2%) patients with perampanel and placebo, respectively. Psychiatric TEAEs were more frequent in patients with psychiatric history for all combined doses and placebo (both P<0.01). Most common psychiatric TEAEs with peram- panel: anxiety (5.3%)/insomnia and aggression (both 2.0%) with/without psychiatric history. In OLEx, 283/1895 (14.9%) patients had psychiatric history. Psychiatric TEAEs occurred in 151 (53.4%)/521 (32.3%) patients with/without psychiatric history (P<0.01); most common psychiatric TEAE: irritability (16.3%/10.4%, with/without psychiatric history). Conclusion: Psychiatric TEAEs were reported by more patients with psychiatric history and were dependent on perampanel dose irrespective of previous psychiatric illness; 2 mg/day and 4 mg/day doses did not increase psychiatric TEAEs. Funding: Eisai Inc. manoj_malhotra@eisai.com